Value of cardiopulmonary exercise test submaximal parameters in the assessment of aortic stenosis patients. (3rd October 2022) - R Santos, R; Paiva, M; Gomes, D; Presume, J; Custodio, P; Andrade, M J; Raposo, L; Durazzo, A; Moreno, L; Mendes, M
Abstract: Background: Exercise test is recommended for risk stratification of asymptomatic patients with severe aortic stenosis (AS), although a significant number of patients can't perform a maximal exercise test, increasing the potential value of sub-maximal parameters for the assessment of these patients. Aim: To assess which parameters could be useful for risk stratification in case of a submaximal Cardiopulmonary Exercise Testing (CPET) in asymptomatic patients with severe AS. Methods: Retrospective evaluation of adult patients with asymptomatic severe AS, in a single center, who underwent CPET between December 2016 and November 2021. All patients underwent a treadmill CPET using an exercise protocol with progressive increase in workload. Patients were divided in group A (maximal CPET) or group B, respectively, if respiratory exchange ratio (RER) was >1.10 at peak exercise or below this value. Known parameters accessed in a submaximal CPET were evaluated: mean minute ventilation/carbon dioxide production slope (VE/VCO2), VO2 value in first ventilatory threshold (VT1), peak circulatory power, and oxygen uptake efficiency slope (OUES). Results: CPET was performed in 25 patients with severe asymptomatic AS (80 years ± 7 years, 56% male), median AVA was 0.86 cm 2 [IQR 0.65–0.95 cm 2 ] and transaortic pressure gradient was 46 mmHg [IQR 41–55 mmHg]. The most used protocol was a ramp slope. Nineteen patients (76%) didn't reach a RER>1.10 (group B) due to respiratory (26%) or peripheral limitation (53%). Comparing both groups, group B patients showed a shorter duration of exercise of (8±3 min vs. 9±4 min, p=0.422), and a lowest mean peak VO2 (16.3±3.6 vs. 20.5±6.9 ml/kg/min, p=0.207). In our population, bivariate analyses demonstrated that OUES was the only submaximal parameter that could discriminate both groups: Group B patients had the lowest values (1.53 [IQR 1.47–1.70] vs. 1.94 [IQR 1.56–2.11], p=0.042). ROC curve analysis of OUES values revealed an AUC of 0.78 (p=0.042) for maximal CPET prediction. The cut-off point with most sensitivity (S) and specificity (E) obtained using the Youden index (0.62) was 1.9 (S≈67%; E≈95%) (Figure 1). Conclusions: In our cohort of asymptomatic AS patients, even with submaximal CPET, OUES accurately identify patients with higher degrees of functional limitation. Whether OUES is useful as prognostic marker to the workflow treatment of AS it's worth to be assessed prospectively. Funding Acknowledgement: Type of funding sources: None.